Is action research necessarily collaborative? Changing mutuality within a project - Sousa, Francisco (2018)
This chapter reports a study on collaboration within an action research project that was conducted by university researchers and elementary school teachers in the Azores, Portugal. More specifically, it examines how different kinds of of participants worked together in different phases of the project. The notion of mutuality (i.e., the relative status of the participants and their ownership of the project) was especially critical for understanding changes in collaboration within the prject. However, mutuality cannot be fully understood if important aspects of the geographical and cultural context in which a project of that kind takes place are not taken into consideration. In this particular case, it is important to consider the fact that local policy is devoid of incentives for elementary school teachers' participation in research projects.